The supervision and transformational leadership styles on nurses' compliance in prevention and control of infection risks at a hospital in Kotamobagu, Indonesia - Widya Astuti; Tri Ismu Pujiyanto; Susi Nurhayati (GHMJ (Global Health Management Journal), 2023)
Background: The quality of health services cannot be separated from the collaboration of all components of human resources, including nurses. Transformational leadership supported by supervision can also improve the prevention and control of infection risk in order to optimize their work performance. Supervision activities carried out by the head of the room might have a positive impact on nurse commitment.  Aims: The objective of this study is to analyze the influence of supervision and transformational leadership style on nurse compliance in infection risk prevention and control at GMIBM (Gereja  Masehi Injili at Bolaang Mongondow) Monompia General Hospital, Kotamobagu, Indonesia. Methods: This original research used an analytic observational with a quantitative approach and a cross sectional study design. A total of 72 nurses who worked at GMIBM Monompia Kotamobagu General Hospital, Kotamobagu Regency, Indonesia, was selected in August 2022 using a total sampling technique based on the data from the human resources division. Two combined questionnaires were distributed to define the leader supervision (20 questions) and the nurses' compliance and their transformational leadership styles (18 questions) for prevention and control the infection risks. The results of this study were analyzed using SPSS Software (univariate and bivariate parameters). Results: This study shows that a sufficient supervision frequency (59.7%) among the participated nurses. We identify there were four transformational leadership styles among the nurses at the selected hospital:  Ideal influence (33.3%), Inspirational motivation (27.8%), Individual consideration (20.8%) and Intellectual stimulation (18.1%). Moreover, the majority of nurses performed good compliance in the preventing and controlling the infection risks (80.6%). The lack of compliance might be significantly resulted by the leader supervisions (p-value: 0.002). By the bivariate analysis, this study suggested that there is a relationship between transformational leadership style and compliance (p value: 0.001). We also noticed that the leader supervision and transformational leadership style are moderating variables to strengthen the nurse compliance (R Square = 0.336). Conclusion : This present study strongly suggested the hospital manager and head departments to pay attention to the two strong factors (Supervision and transformational leadership style) affecting the nurses compliance in updating and implementing the prevention and risk control programs.